2023
DOI: 10.3390/foods12061306
|View full text |Cite
|
Sign up to set email alerts
|

Research on Influencing Factors of Food Choice and Food Consumption

Abstract: Nowadays, most consumers are well aware of what makes up a healthy and sustainable diet [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Individuals with higher levels of openness are generally more adventurous and curious, making them more inclined to explore diverse cuisines and try unfamiliar foods. Cultural factors, exposure to different culinary traditions, and the influence of social and environmental factors also play a role in shaping attitudes of individuals toward new foods (Geuens, 2023). Additionally, positive or negative experiences with trying new foods in the past can impact the willingness of a person to experiment with novel culinary options.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher levels of openness are generally more adventurous and curious, making them more inclined to explore diverse cuisines and try unfamiliar foods. Cultural factors, exposure to different culinary traditions, and the influence of social and environmental factors also play a role in shaping attitudes of individuals toward new foods (Geuens, 2023). Additionally, positive or negative experiences with trying new foods in the past can impact the willingness of a person to experiment with novel culinary options.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence shows the impact of food choices on human health and the environment, only 5.4% of adults in Australia met the fruit and vegetable recommendation in 2017–2018 (two or more servings for women and five or more servings for men) [ 46 ]. Many social determinants can impact eating habits, such as a lack of access and money constrains [ 47 ], cultural determinants [ 48 , 49 ] and food and nutritional knowledge [ 50 , 51 , 52 , 53 ]. Studies have shown the importance of understanding the impacts of food choices on the environment and more sustainable eating habits [ 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%